Cell-in-Cell: From Cell Biology to Translational Medicine. (14th September 2022) - Chen, Qiao; Wang, Xiaoning; He, Meifang
Abstract : Cell-in-cell structures (CICs) refer to cytoplasmic internalization of a cell by another cell, which are found throughout various biological systems and have been a part of scientific dogma for a long time. However, neither the mechanisms underlying this phenomenon nor their possible roles in disease development have resulted in major breakthroughs until recent years. In view of the ubiquity of CICs in inflammatory tissue and tumors, it is tempting to think that these specific structures could be associated with clinical diagnosis and treatment and thus would become a new hotspot for translational medicine. Translational medicine is a new concept in the field of international biomedical research that appeared in the last 20 years, which transforms basic research into clinical application. With the growing interest in this field, this review addresses recent research on CICs and their potential clinical implications in cytomorphological diagnosis and the pathology of human diseases, while discussing as yet unanswered questions. We also put forward future directions to reduce the gap in our knowledge caused by our currently limited understanding of CICs.